The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/gene.20146
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic expression of Cre recombinase in mitral/tufted cells of the olfactory bulb

Abstract: Olfactory information is conveyed from the periphery to the olfactory cortices through mitral and tufted (M/T) cells in the olfactory bulb. A mouse with a specific expression of Cre recombinase in M/T cells is essential for genetic marking of M/T cells and manipulating their properties. Protocadherin 21 (Pcdh21) expression is highly restricted to M/T cells. Here we report a transgenic mouse line, Pcdh21-Cre, in which 10-kb mouse Pcdh21 promoter drives the expression of Cre recombinase. In Pcdh21-Cre mice, Cre … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 24 publications
(20 reference statements)
2
89
0
Order By: Relevance
“…The NT-GFP mouse strain may greatly aid in screening for molecules involved in LOT establishment and collateral branching. Recently, a mouse line was reported that expresses Cre recombinase almost exclusively within M/T cells in both the MOB and the accessory olfactory bulb, using the protocadherin 21 promoter (Nagai et al, 2005). When crossed to a reporter strain, a staining pattern that is very similar to the NT-GFP mouse was detected in the MOB and LOT of young mice.…”
Section: Discussionmentioning
confidence: 97%
“…The NT-GFP mouse strain may greatly aid in screening for molecules involved in LOT establishment and collateral branching. Recently, a mouse line was reported that expresses Cre recombinase almost exclusively within M/T cells in both the MOB and the accessory olfactory bulb, using the protocadherin 21 promoter (Nagai et al, 2005). When crossed to a reporter strain, a staining pattern that is very similar to the NT-GFP mouse was detected in the MOB and LOT of young mice.…”
Section: Discussionmentioning
confidence: 97%
“…A DNA fragment containing the tetO promoter (Gossen and Bujard, 1992) followed by an ecliptic synaptopHluorin (kindly gifted by Dr. Miesenbock, Yale University, New Haven, CT) (Miesenbock et al, 1998) and a rabbit ␤-globin intron/ polyadenylation signal was excised from the vector by digestion at insertflanking AscI sites, gel purified, and microinjected into the pronuclei of fertilized eggs from C57BL/6CrSlc mice (provided by Japan SLC, Hamamatsu, Japan) to generate tetO-synaptopHluorin transgenic mice, as described previously (Nagai et al, 2005). The genotype of the animals was determined by PCR of tail genomic DNA with primers unique to the transgene (5Ј-CTTTTCACTGGAGTTGTCCCAATTC, 5Ј-CCAAT TTGTGTCCAAGAATGTTTCC).…”
Section: Generation Of Transgenic Mice and Mice With Targeted Allelesmentioning
confidence: 99%
“…The tissue was then frozen in OCT compound (Tissue-Tek; Sakura, Tokyo, Japan), and 30 -40 m parasagittal or coronal sections were cut on a cryostat. Sections were treated according to standard histochemistry protocols, as described previously (Nagai et al, 2005). Primary antibodies against vesicular GABA transporter (VGAT) (1:2000; Millipore, Temecula, CA), gephyrin (1:300; Synaptic Systems, Goettingen, Germany), MCH (1:3000; Millipore), and orexin-A, and -B (1:20000; kindly gifted from Dr.…”
Section: Immunohistochemistry Fluorescent Nissl Staining and Microsmentioning
confidence: 99%
“…As anticipated, the GFP+ cell population showed significant expression of 11 genes that are known to express in developing OB projection neurons. These genes include Tbr1 , Eomes (also known as Tbr2) (Imamura and Greer, 2013), Cdhr1 ( Pcdh21 ) (Nagai et al, 2005), Slc17a7 ( vGluT1) (Gabellec et al, 2007), Tfap2e (AP2ε) (Feng et al, 2009), Reelin (Imamura et al, 2006), Emx1, Emx2 (Mallamaci et al, 1998), Sall1 (Harrison et al, 2007), Nrp1 , and L1cam (Inaki et al, 2004). While less or no expression was observed for 12 genes whose expression in OB projection neurons is not observed.…”
Section: Resultsmentioning
confidence: 99%